Arginine metabolism and neurocognitive impairment in offspring of bipolar parents: a high-risk case-control study - Arıcı Sağlıyan, Gökçeçiçek; Çetin, Fatih Hilmi; Akyürek, Fikret; Tok, Oğuzhan; Çiçek Zekey, Özlem; Tezcan, Mustafa Esad; Sağlıyan, Bilal; Türkoğlu, Serhat; Uçar, Halit Necmi; Öztürk, Bahadır; Altınbaş, Kürşat (Frontiers in Psychiatry, 2025)
IntroductionThe aim of this study is to investigate whether arginine and its metabolites can be an endophenotype for bipolar disorder (BD) and to evaluate the role of arginine metabolites and neurocognitive function levels in unaffected healthy children of parents diagnosed with BD in cognitive impairment.MethodsThe study included 37 healthy children of parents diagnosed with BD Type I as the high-risk group and 36 healthy children of parents without any psychiatric disorders as the control group. The arginine, n-monomethyl-l-arginine acetate (L-NMMA), asymmetric dimethylarginine (ADMA), symmetric dimethylarginine (SDMA), citrulline, homoarginine, ornithine serum levels, and nitric oxide synthase (NOS) activity level of both groups were compared.ResultsThe study found that in the high-risk group, ADMA, SDMA, and ornithine levels were significantly higher compared to the controls, while citrulline and NOS activity level were significantly lower in the high-risk group compared to the controls. All neurocognitive performances of the high-risk group were considered statistically significantly worse compared to controls. The impairment in neurocognitive functions in the high-risk group was found to be correlated with ADMA, L-NMMA, citrulline, homoarginine, ornithine levels, and NOS activity level.DiscussionThese findings highlight a potential link between arginine metabolism and executive dysfunction in individuals at high risk for BD. Further longitudinal studies are essential to fully understand the complex interactions between these factors.